(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article focuses on the importance of comparing the genres of discourse analysis, highlighting their communicative and stylistic features, and considering them in accordance with linguistic concepts. In addition, the transversal view allows to compare the genres of legal discourse in French and Uzbek languages.